Stable isotope and Ar/Ar evidence of prolonged multiscale fluid flow during exhumation of orogenic crust: Example from the Mont Blanc and Aar Massifs (NW Alps). Issue 9 (12th September 2014) - Rossi, M.; Rolland, Y.
Abstract The spatial and temporal scales and the geometry of fluid pathways in a collisional orogen are investigated using stable isotope analysis (O, C, and H) and 40Ar/39Ar dating of vein minerals formed at circa 11–16 Ma in the Mont Blanc and the Aar External Crystalline Massifs. In both massifs 40Ar/39Ar dating of veins adularia provides evidence for progressive crystallization from 16 to 9 Ma, and mainly at 11–12 Ma following veins opening during shear zone activity. The fluid flow duration thus ranges from 4 to 5 Ma in the two massifs. The δ18O values of vein quartz and calcite are similar to those of undeformed crystalline and sedimentary host rocks, suggesting rock buffering, while carbon isotope ratios of vein calcites fall into three compositional groups. A‐type veins have δ13C values that are buffered by the Helvetic metasediments, which suggests that these veins formed in a closed system from a locally derived CO2‐rich fluid. The fluid in equilibrium with C‐type veins has depleted δ13C values similar to mantle‐CO2, while the intermediate δ13C values of B‐type veins suggest mixing between the A‐type and C‐type fluids. These results are in agreement with crustal‐ to lithosphere‐scale upward vertical fluid flow along vertical shear zones related to the strike‐slip system bounding the Adriatic block since 16–20 Ma, connecting a deep‐seated fluid to some downward flow in the sedimentary cover of External Crystalline Massifs.